IRANIAN PRESIDENTS AND TAJIK-IRANIAN RELATIONS - ABDULLO, Rashid (CENTRAL ASIA AND THE CAUCASUS, 2013)
The author examines the relations between Tajikistan and Iran in the context of the political processes occurring in Iran. Throughout the twenty years of Tajikistan’s independence, these relations have passed through different stages, each marked by Tehran’s political course and the personalities of each of the Iranian presidents. At the early stages, the flexible and cautious Rafsanjani preferred to limit contacts to cultural cooperation; Tehran, however, did not shy away from involvement in the domestic conflict in Tajikistan as a broker, and its positive contribution cannot be overestimated. This was when the two countries set up a base for closer trade and economic contacts; they encouraged business trips and tourism in an effort to become better acquainted with each other. Under President Khatami, bilateral relations acquired an even stronger economic bias. Iranian investments helped to implement several large-scale strategic infrastructural projects initiated by the government of Tajikistan. It was during the presidency of Mahmoud Ahmadinejad that relations between the two countries reached a new and higher level: Iran became a strategic partner and the largest investor. Tehran invested in strategically important projects in energy, transport, and communication. Recently elected President Hassan Rouhani, known as a subtle politician and diplomat, will probably change the development vector of relations between the two countries.